Effects of debinding and sintering atmosphere on properties and corrosion resistance of powder injection molded 316 L - Stainless steel - Raza, M.R. (Penerbit Universiti Kebangsaan Malaysia, 2017)
316L stainless steel is a common biomedical material. Currently, biomedical parts are produced through powder injection molding (PIM). Carbon control is the most critical in PIM. Improper debinding can significantly change the properties of the final product. In this work, thermal debinding and sintering were performed in two different furnaces (i.e. laboratory and commercially available furnaces) to study the mechanical properties and corrosion resistance. Debounded samples were sintered in different atmospheres. The samples sintered in inert gas showed enhanced mechanical properties compared with wrought 316L stainless steel and higher corrosion rate than those sintered in the vacuum furnace. The densification and tensile strength of the hydrogen sintered samples increased up to 3 and 51, respectively, compared with those of the vacuum-sintered samples. However, the samples sintered in inert gas also exhibited reduced ductility and corrosion resistance. This finding is attributed to the presence of residual carbon in debonded samples during debinding.